Social housing policy or social policy for housing? The role of the Programa Especial de Realojamento (PER) in the housing/planning nexus in Portugal - Tulumello, S.; Ferreira, A. C.; Colombo, A.; Di Giovanni, C.; Allegra, M. (Lisbon AESOP Annual Congress ’17: Spaces for dialog for places of dignity: book of proceedings, 2017)
Recent (European) comparative studies in the fields of housing policy and spatial planning have been dominated by taxonomical approaches (attempts at categorising systems and temporal stages of state action) and measures of the ‘maturity’ of national systems. In this paper, we adopt a genealogical perspective and consider (national and local) cultures central to the shaping of policy (differences and convergence). We set out a long-term, in-depth exploration of the planning-housing nexus in Portugal – a case that helps adding nuances to mainstream theorisation – and focus on the Programa Especial de Relojamento (PER; Special Programme for Rehousing), a programme that has had changing roles (from a financial instrument to a core component of policies of urban regeneration) in connection with political and planning cultures changing in time and space. Our goal is contributing to making sense of the intersection between planning cultures in transition and changing housing policy, namely the generalised shift toward regeneration and concurrent retrenchment of state action – and the relation among housing as welfare (‘social housing policy’) and housing as urban policy (‘social policy for housing’).